Pancasila as the Ideology of National Development - Winda Agustari; Ziyadatul Widad; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Abstract - This article aims to find out the concept of Pancasila as a National Development Ideology by examining Pancasila as a development paradigm. Development includes economic development, education and science and technology. The term paradigm contains the connotation of understanding as a source of values, framework of thought, basic orientation, source of principles, directions, and processes in certain fields including the field of development. The problem is that the development orientation is more focused in dealing with the development of national ideology, causing the goal in the formation of the nation's personality to be reduced. This was followed by a weakening of the nation's character. Development will not be great if it is not based on the values ​​embodied in the nation's morals, so a development reorientation is needed that refers to the Pancasila State philosophy, because basically Pancasila is a paradigm in development. Pancasila plays a role in providing several ethical principles for economic development, education and science and technology